ANALISIS KESULITAN BELAJAR MATEMATIKA SISWA BERKEBUTUHAN KHUSUS SLOW LEANER DI KELAS 1 SDN SAMADIKUN - Wahyu Adi Pratama; Dina Pratiwi Dwi Santi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is the right of all children, including children with special needs elow learner even though they often experience learning difficulties, especially in mathematics learning, this is the basis for this research. This study aims to analyze the learning difficulties experienced by students with special needs of the slow learner type in grade I of elementary school and the efforts of teachers in overcoming these obstacles. The subjects of this study were 2 students with special needs elow learner, namely student (A) and student (E) in grade 1 of SDN Samadikun. The research approach used was qualitative with a case study. Data collection techniques through direct observation in class, interviews with teachers, interviews with parents of students with special needs and written tests. The results of the study showed that slow learner students in grade I had difficulty understanding oral instructions, were slow in absorbing lesson materials, and had low memory which affected overall academic achievement. In addition, students also experienced obstacles in the social emotional aspect, such as lack of self-confidence and easily feeling anxious in learning situations. Teachers face challenges in delivering material repeatedly and must adjust learning strategies, such as the use of visual media, individual approaches, and providing positive reinforcement consistently. The role of parents is also clearly visible in efforts to help slow learners with special needs students with learning difficulties in mathematics